A long-period quaternary oxide thermal barrier coating material with high fracture toughness and a preparation method thereof

CN118955125BActive Publication Date: 2026-10-27XIDIAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411006420.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2026-10-27
Estimated Expiration
2044-07-25

AI Technical Summary

Technical Problem

[0004]为了克服上述现有技术中的缺点,本发明的目的在于提供一种长周期四元氧化物热障涂层材料及其制备方法,通过掺杂元素Me,Me为Zr、Gd、Y、Nb、Ti中的一种,优化四元氧化物的组分,利用高温固相反应合成技术,成功制备出具有优异热稳定性和高断裂韧性的热障涂层材料,能够解决现有技术中热障涂层易剥落、寿命短的技术问题;此外,本发明的制备方法工艺简单,可操作性强,适合大规模生产,通过本发明制备方法制备得到的MexHf6Ta2O17+y热障涂层材料能够用于航空航天、发电设备等高温环境中

Benefits of technology

[0023]1.本发明采用粒径为1-3μm的金属氧化物原料,粒径均匀差异小,使不同金属氧化物粉末之间充分反应,降低了材料中可能存在的局部缺陷和不均匀结构,提高了材料的均质性和性能的一致性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118955125B_ABST
    Figure CN118955125B_ABST
Patent Text Reader

Abstract

This invention discloses a high fracture toughness long-period quaternary oxide thermal barrier coating material and its preparation method. The material is a long-period quaternary single-phase solid solution oxide with the chemical formula Me. x Hf6Ta2O 17+y The doping element Me is one of Zr, Gd, Y, Nb, and Ti. By introducing the doping element Me, the composition of the quaternary oxide is optimized, and a thermal barrier coating material with excellent thermal stability and high fracture toughness is prepared by using high-temperature solid-state reaction synthesis technology. The thermal barrier coating material prepared by this invention has the characteristics of uniform composition, high density, high chemical purity, and high fracture toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of thermal barrier coating materials, and particularly relates to a high fracture toughness long-period quaternary oxide thermal barrier coating material and its preparation method. Background Technology

[0002] With the continuous improvement of the thrust-to-weight ratio of high-performance aero-engines, turbine blades are required to withstand higher temperatures. In 1953, NASA proposed coating the surface of high-temperature alloy blades with a high-temperature resistant and highly insulating protective coating system, namely thermal barrier coating (TBC). Studies have shown that a 250μm thick TBC can reduce the substrate temperature by 110–170°C. Therefore, TBC is considered the most practical technology to significantly increase the service temperature of aero-engine turbine blades and has become an indispensable thermal protection material for the hot-end components of aero-engine turbine blades, greatly determining the performance and development level of the engine. Currently, the TBC material used in in-service aero-engine turbine blades is yttrium-stabilized zirconium oxide, but this coating undergoes a phase transformation after long-term service in environments above 1200°C, leading to a sharp decrease in service life.

[0003] Chinese invention patent CN114368969A discloses a TiSi2-doped Gd2Zr2O7 ceramic material, its preparation method, and a thermal barrier coating. The method utilizes TiSi2 to dope the Gd2Zr2O7 thermal barrier coating ceramic material. The prepared thermal barrier coating exhibits a fracture toughness of only 1.83 MPa·m at room temperature. 1 / 2 The invention patent with announcement number CN111925211B discloses an A2B2O7 type rare earth tantalate ceramic and its preparation method. According to the structural formula of RE2MTaO7, RE2O3 and M2O3 are dissolved in concentrated nitric acid for reaction, and the pH is adjusted to not less than 1.5. Then, TaOCl3 solution is added dropwise with continuous stirring, and ammonia water is added simultaneously to stabilize the pH of the system at 9-10. Stirring continues in a water bath environment, and the precipitate is washed with deionized water until pH=7. The resulting filter cake is dried in an oven and then sieved for later use. The powder is placed in a graphite mold and subjected to spark plasma sintering in a sintering furnace. The sintered sample is then annealed to remove carbon, yielding a dense RE2MTaO7 bulk. The RE2MTaO7 bulk has a strength of approximately 1.7 MPa·m. 1 / 2 The fracture toughness of the ceramic materials in the above-mentioned prior art is all above 2.0 MPa·m. 1 / 2 The following factors result in a limited high-temperature service life, making it unsuitable for industrial production. Summary of the Invention

[0004] To overcome the shortcomings of the prior art, the present invention aims to provide a long-period quaternary oxide thermal barrier coating material and its preparation method. By doping with the element Me (one of Zr, Gd, Y, Nb, and Ti) to optimize the composition of the quaternary oxide, and utilizing high-temperature solid-state reaction synthesis technology, a thermal barrier coating material with excellent thermal stability and high fracture toughness is successfully prepared. This solves the technical problems of easy peeling and short lifespan of thermal barrier coatings in the prior art. Furthermore, the preparation method of the present invention is simple, highly operable, and suitable for large-scale production. The Me prepared by the method of the present invention... x Hf6Ta2O 17+y Thermal barrier coating materials can be used in high-temperature environments such as aerospace and power generation equipment.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0006] A high fracture toughness long-period quaternary oxide thermal barrier coating material, wherein the thermal barrier coating material is a long-period quaternary single-phase solid solution oxide with the chemical formula Me. x Hf6Ta2O 17+y The doping element Me is one of Zr, Gd, Y, Nb, or Ti. When Me is Zr, x = 3 and y = 6; when Me is Y, x = 4 and y = 6; when Me is Gd, x = 2 and y = 3; when Me is Nb, x = 2 and y = 5; and when Me is Ti, x = 2 and y = 4.

[0007] The raw material for the thermal barrier coating material includes Me. x O y HfO2 and Ta2O5, of which Me x O y The molar ratio of HfO2 and Ta2O5 is (1-3):6:1; the Me x O y The particle size of HfO2 and Ta2O5 is 1-3 μm.

[0008] A method for preparing a high fracture toughness, long-period quaternary oxide thermal barrier coating material as described above includes the following steps:

[0009] Step 1: Prepare raw material Me x O y HfO2 and Ta2O5 were wet-milled to obtain a mixed slurry; Me x O y :HfO2:Ta2O5=(1-3):6:1;

[0010] Step 2: Heat and dry the mixed slurry obtained in Step 1, then grind it to obtain a mixed powder with a particle size greater than 100 mesh;

[0011] Step 3: Calcine the mixed powder obtained in Step 2 at 1100-1300℃ in air or oxygen atmosphere for 6-9 hours to obtain Me powder. x Hf6Ta2O 17+y Thermal barrier coating materials are powder-based, high fracture toughness, long-period quaternary oxide thermal barrier coating materials.

[0012] In step 1, Me x O y The purity of the powders of HfO2 and Ta2O5 is ≥99%.

[0013] In step 1, the ball milling time is 4-8 hours, zirconium oxide balls are used as the ball milling medium, anhydrous ethanol is used as the liquid medium, the ball-to-material ratio is 3:1, and the rotation speed is 300-350 r / min.

[0014] In step 2, a magnetic stirrer is used for heating and drying, with a stirring speed of 1000-1500 r / min and a heating temperature of 180-220℃.

[0015] The preparation method of the present invention further includes:

[0016] Step 4: Apply the adhesive Me, which was in powder form in step 3. x Hf6Ta2O 17+y The thermal barrier coating material is granulated and then sieved to obtain agglomerated powder with a sieve mesh size of 100-200 mesh.

[0017] Step 5: Pre-press the agglomerated powder obtained in Step 4 to obtain a green preform; then perform cold isostatic pressing on the green preform to obtain Me. x Hf6Ta2O 17+y Ceramic blank;

[0018] Step 6: Take the Me obtained in Step 5 x Hf6Ta2O 17+y The ceramic body is debinded, then calcined at 1500-1800℃ for 6-9 hours, and cooled to room temperature in the furnace to obtain a bulk Me. x Hf6Ta2O 17+y Thermal barrier coating materials are bulk, high fracture toughness, long-period quaternary oxide thermal barrier coating materials.

[0019] In step 4, the adhesive is a polyvinyl alcohol solution or a polyvinylpyrrolidone solution, with a mass fraction of 1-3%, and the mass of the adhesive incorporated accounts for a significant portion of the powder in step 3. x Hf6Ta2O 17+y The thermal barrier coating material accounts for 0.2-0.6% of the material's mass.

[0020] The pressure for pre-pressing in step 5 is 100-150 MPa; the pressure for cold isostatic pressing is 150-280 MPa, and the holding time is 10-30 min.

[0021] The glue removal operation in step 6 specifically involves: removing the glue from Me... x Hf6Ta2O 17+y The ceramic body is placed in an air or oxygen atmosphere and kept at 400-600℃ for 4-6 hours.

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0023] 1. This invention uses metal oxide raw materials with a particle size of 1-3μm. The uniform particle size and small difference allow for full reaction between different metal oxide powders, reducing potential local defects and non-uniform structures in the material, and improving the homogeneity and performance consistency of the material.

[0024] 2. This invention uses a metal oxide of one of Zr, Gd, Y, Nb, and Ti to prepare a quaternary oxide thermal barrier coating material. The selected metal ions have relatively small radii, which makes it easier for them to diffuse into each other at high temperatures, promoting the formation of single-phase oxides, enhancing the reaction efficiency between different components during sintering, and reducing sintering defects.

[0025] 3. The evaporation drying process used in this invention ensures that the ball-milled slurry remains uniformly mixed during the drying process, preventing stratification due to differences in the relative molecular mass of the raw materials. This guarantees that the oxide raw materials can fully react during sintering, improving the homogeneity and performance stability of the material, meeting usage requirements, and significantly enhancing the quality and reliability of the final product.

[0026] 4. The solid-state sintering process used in this invention to synthesize thermal barrier coating materials does not introduce foreign phases, thus avoiding material contamination during the preparation process and obtaining thermal barrier coating materials with uniform composition, high density, and high chemical purity.

[0027] 5. This invention optimizes the composition of quaternary oxides by doping with one of Zr, Gd, Y, Nb, or Ti, thus preparing a long-period quaternary oxide thermal barrier coating material. Compared with existing ternary oxide thermal barrier coating materials, this material has a fracture toughness of at least 2.0 MPa·m. 1 / 2 This improves its high-temperature service life.

[0028] In summary, this invention optimizes the composition of quaternary oxides by doping with one of Zr, Gd, Y, Nb, or Ti, thereby preparing long-period quaternary oxides Me. x Hf6Ta2O 17+yThe thermal barrier coating material remains single-phase, and compared with other single-phase ternary rare-earth tantalate thermal barrier coating materials, the thermal barrier coating material prepared by this invention exhibits significantly improved fracture toughness, with an improvement exceeding 30%. Therefore, the Me prepared by this invention... x Hf6Ta2O 17+y Thermal barrier coating materials are expected to be applied to turbine blades of aero-engines, enabling thermal barrier coatings to serve at high temperatures for a long service life, thus having greater practical value. Attached Figure Description

[0029] Figure 1 Me provided by the present invention x Hf6Ta2O 17+y XRD pattern of thermal barrier coating material.

[0030] Figure 2 Zr3Hf6Ta2O provided in Embodiment 1 of the present invention 23 SEM image of thermal barrier coating material.

[0031] Figure 3 Zr3Hf6Ta2O provided in Embodiment 1 of the present invention 23 TEM images of thermal barrier coating materials, in which... Figure 3 (a) is low resolution. Figure 3 (b) is high resolution. Figure 3 (c) is the EDX surface scan of the Hf element. Figure 3 (d) is the EDX surface scan of Zr element, and (e) is the EDX surface scan of Ta element. Figure 3 (f) is the EDX surface scan of element O. Detailed Implementation

[0032] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments.

[0033] A high fracture toughness long-period quaternary oxide thermal barrier coating material, wherein the thermal barrier coating material is a long-period quaternary single-phase solid solution oxide with the chemical formula Me. x Hf6Ta2O 17+y The doping element Me is one of Zr, Gd, Y, Nb, or Ti. Specifically, when Me is Zr, x = 3 and y = 6; when Me is Y, x = 4 and y = 6; when Me is Gd, x = 2 and y = 3; when Me is Nb, x = 2 and y = 5; and when Me is Ti, x = 2 and y = 4. The raw material for this thermal barrier coating material includes Me. x O y HfO2 and Ta2O5, of which Me x O y The molar ratio of HfO2 and Ta2O5 is (1-3):6:1; the Me xO y The particle size of HfO2 and Ta2O5 is 1-3 μm.

[0034] A method for preparing a long-period quaternary oxide thermal barrier coating material with high fracture toughness includes the following steps:

[0035] Step 1: Prepare raw material Me x O y HfO2 and Ta2O5 were wet-milled for 4-8 hours to obtain a mixed slurry; zirconia balls were used as the milling medium, anhydrous ethanol was used as the liquid medium, the ball-to-material ratio was 3:1, and the rotation speed was 300-350 r / min; Me x O y :HfO2:Ta2O5=(1-3):6:1,Me x O y The purity of the powders of HfO2 and Ta2O5 is ≥99%; the Me x O y The particle size of HfO2 and Ta2O5 is 1-3 μm;

[0036] Step 2: The mixed slurry obtained in Step 1 is heated and dried using a magnetic stirrer to prevent the oxides from separating during drying due to their different relative molecular masses. The magnetic stirrer speed is 1000-1500 r / min and the heating temperature is 180-220℃. Then, it is ground to obtain a mixed powder with uniform particle size and a particle size greater than 100 mesh.

[0037] Step 3: The mixed powder obtained in Step 2 is calcined at 1100-1300℃ in air or oxygen atmosphere for 6-9 hours. This allows for interdiffusion of atoms on the surface of the solid particles, resulting in chemical reactions and initial grain growth, yielding Me powder. x Hf6Ta2O 17+y Thermal barrier coating materials, specifically high fracture toughness, long-period quaternary oxide thermal barrier coating materials in powder form, wherein the reaction equation is Me x O y +6HfO2+Ta2O5=Me x Hf6Ta2O 17+y ;

[0038] Step 4: Add the adhesive to the powdered Me from Step 3. x Hf6Ta2O 17+y The thermal barrier coating material is granulated and then sieved to obtain agglomerated powder with a sieve mesh size of 100-200 mesh. The adhesive is a polyvinyl alcohol solution or a polyvinylpyrrolidone solution, with a mass fraction of 1-3%, and the mass of the adhesive incorporated accounts for a percentage of the powder obtained in step 3. x Hf6Ta2O 17+y0.2-0.6% of the mass of the thermal barrier coating material;

[0039] Step 5: Using a 20mm diameter mold, pre-press the agglomerated powder obtained in Step 4 to obtain a green blank. The pre-pressing pressure is 100-150MPa. Then, the green blank is subjected to cold isostatic pressing to obtain Me. x Hf6Ta2O 17+y The ceramic preform is subjected to a cold isostatic pressing pressure of 150-280 MPa and a holding time of 10-30 min.

[0040] Step 6: Take the Me obtained in Step 5 x Hf6Ta2O 17+y The ceramic green body is placed in an air or oxygen atmosphere and held at 400-600℃ for 4-6 hours to remove the binder, allowing it to decompose and volatilize, thus preventing high-temperature carbonization and contamination of the green body. It is then calcined at 1500-1800℃ for 6-9 hours, allowing the grains to grow, combine, and fill the voids to achieve densification. Finally, it is cooled to room temperature in the furnace to obtain a high-density, bulk Me. x Hf6Ta2O 17+y Thermal barrier coating materials are bulk, high fracture toughness, long-period quaternary oxide thermal barrier coating materials.

[0041] The fracture toughness of the bulk thermal barrier coating material is at least 2.0 MPa·m. 1 / 2 .

[0042] Example 1

[0043] A Zr3Hf6Ta2O 23 A thermal barrier coating material, wherein the raw materials of the thermal barrier coating material include ZrO2, HfO2 and Ta2O5, wherein the molar ratio of ZrO2, HfO2 and Ta2O5 is 3:6:1.

[0044] A Zr3Hf6Ta2O 23 The preparation method of thermal barrier coating materials includes the following steps:

[0045] Step 1: The raw materials ZrO2, HfO2 and Ta2O5 with a molar ratio of 3:6:1 are wet ball-milled at 300 r / min for 6 h to obtain a mixed slurry; the particle size of ZrO2, HfO2 and Ta2O5 is 1-3 μm and the purity is 99%;

[0046] Step 2: The mixed slurry obtained in Step 1 is evaporated at 1000 r / min and 180℃, and then ground to obtain a mixed powder with uniform particle size and greater than 100 mesh.

[0047] Step 3: The mixed powder obtained in Step 2 was calcined at 1100℃ in air atmosphere for 9 hours, and then cooled to room temperature in the furnace to obtain Zr3Hf6Ta2O in powder form. 23 Thermal barrier coating materials;

[0048] Step 4: Add a 2% (w / w) polyvinyl alcohol solution to the Zr3Hf6Ta2O powder from Step 3. 23 The thermal barrier coating material is granulated and sieved to obtain agglomerated powder with a sieve mesh size of 100-200 mesh. The mass of the binder incorporated accounts for a certain percentage of the Zr3Hf6Ta2O powder obtained in step 3. 23 0.4% of the mass of the thermal barrier coating material;

[0049] Step 5: The agglomerated powder obtained in Step 4 is pre-pressed at 150 MPa to obtain a green preform. Then, the green preform is cold isostatically pressed at 280 MPa for 10 min to obtain Zr3Hf6Ta2O. 23 Ceramic blank;

[0050] Step 6: Take the Zr3Hf6Ta2O obtained in Step 5 23 The ceramic body was held at 600℃ for 4 hours in air to remove the binder, followed by calcination at 1500℃ for 9 hours, and then cooled to room temperature in the furnace to obtain a bulk Zr3Hf6Ta2O. 23 Thermal barrier coating materials.

[0051] The blocky Zr3Hf6Ta2O 23 The fracture toughness of the thermal barrier coating material is 2.43 ± 0.09 MPa·m. 1 / 2 .

[0052] Example 2

[0053] A Gd2Hf6Ta2O 20 A thermal barrier coating material, wherein the raw materials of the thermal barrier coating material include Gd2O3, HfO2 and Ta2O5, wherein the molar ratio of Gd2O3, HfO2 and Ta2O5 is 1:6:1.

[0054] A Gd2Hf6Ta2O 20 The preparation method of thermal barrier coating materials includes the following steps:

[0055] Step 1: Gd2O3, HfO2 and Ta2O5 with a raw material molar ratio of 1:6:1 are wet ball-milled at 320 r / min for 7 h to obtain a mixed slurry; the particle size of Gd2O3, HfO2 and Ta2O5 is 1-3 μm and the purity is 99%;

[0056] Step 2: The mixed slurry obtained in Step 1 is evaporated at 1100 r / min and 190℃, and then ground to obtain a mixed powder with uniform particle size and greater than 100 mesh.

[0057] Step 3: The mixed powder obtained in Step 2 was calcined at 1200℃ in an oxygen atmosphere for 6 hours, and then cooled to room temperature in the furnace to obtain Gd2Hf6Ta2O in powder form. 20 Thermal barrier coating materials;

[0058] Step 4: Add a 3% (w / w) polyvinylpyrrolidone solution to the powdered Gd2Hf6Ta2O from Step 3. 20 The thermal barrier coating material is granulated and sieved to obtain agglomerated powder with a sieve mesh size of 100-200 mesh. The mass of the binder incorporated accounts for a certain percentage of the Gd2Hf6Ta2O powder obtained in step 3. 20 0.6% of the mass of the thermal barrier coating material;

[0059] Step 5: The agglomerated powder obtained in Step 4 is pre-pressed at 120 MPa to obtain a green body, and then the green body is cold isostatically pressed at 200 MPa for 15 min to obtain Gd2Hf6Ta2O. 20 Ceramic blank;

[0060] Step 6: Take the Gd2Hf6Ta2O obtained in Step 5 20 The ceramic body was placed in an oxygen atmosphere and held at 400℃ for 6 hours to remove the binder, followed by calcination at 1800℃ for 8 hours, and then cooled to room temperature in the furnace to obtain bulk Gd2Hf6Ta2O. 20 Thermal barrier coating materials.

[0061] The bulk Gd2Hf6Ta2O 20 The fracture toughness of the thermal barrier coating material is 2.26 ± 0.09 MPa·m. 1 / 2 .

[0062] Example 3

[0063] A Y4Hf6Ta2O 23 A thermal barrier coating material, wherein the raw materials of the thermal barrier coating material include Y2O3, HfO2 and Ta2O5, wherein the molar ratio of Y2O3, HfO2 and Ta2O5 is 2:6:1.

[0064] A Y4Hf6Ta2O 23 The preparation method of thermal barrier coating materials includes the following steps:

[0065] Step 1: The raw materials Y2O3, HfO2 and Ta2O5 with a molar ratio of 2:6:1 are wet ball-milled at 340 r / min for 5 h to obtain a mixed slurry; the particle size of Y2O3, HfO2 and Ta2O5 is 1-3 μm and the purity is 99%;

[0066] Step 2: The mixed slurry obtained in Step 1 is evaporated at 1200 r / min and 200℃, and then ground to obtain a mixed powder with uniform particle size and greater than 100 mesh.

[0067] Step 3: The mixed powder obtained in Step 2 was calcined at 1300℃ in air for 7 hours, and then cooled to room temperature in the furnace to obtain Y4Hf6Ta2O in powder form. 23 Thermal barrier coating materials;

[0068] Step 4: Add a 3% (w / w) polyvinyl alcohol solution to the powdered Y4Hf6Ta2O from Step 3. 23 The thermal barrier coating material is granulated and sieved to obtain agglomerated powder with a sieve mesh size of 100-200 mesh. The mass of the binder incorporated accounts for a certain percentage of the Y4Hf6Ta2O powder obtained in step 3. 23 0.6% of the mass of the thermal barrier coating material;

[0069] Step 5: The agglomerated powder obtained in Step 4 is pre-pressed at 100 MPa to obtain a green preform. Then, the green preform is cold isostatically pressed at 260 MPa for 20 min to obtain Y4Hf6Ta2O. 23 ceramic body,

[0070] Step 6: Take the Y4Hf6Ta2O obtained in Step 5 23 The ceramic body was placed in air and held at 600℃ for 5 hours to remove the binder, followed by calcination at 1700℃ for 6 hours, and then cooled to room temperature in the furnace to obtain bulk Y4Hf6Ta2O. 23 Thermal barrier coating materials.

[0071] The blocky Y4Hf6Ta2O 23 The fracture toughness of the thermal barrier coating material is 2.36 ± 0.29 MPa·m. 1 / 2 .

[0072] Example 4

[0073] A Nb2Hf6Ta2O 22 A thermal barrier coating material, wherein the raw materials of the thermal barrier coating material include Nb2O5, HfO2 and Ta2O5, wherein the molar ratio of Nb2O5, HfO2 and Ta2O5 is 1:6:1.

[0074] A Nb2Hf6Ta2O 22The preparation method of thermal barrier coating materials includes the following steps:

[0075] Step 1: Nb2O5, HfO2 and Ta2O5 with a raw material molar ratio of 1:6:1 are wet ball-milled at 350 r / min for 4 h to obtain a mixed slurry; the particle size of Nb2O5, HfO2 and Ta2O5 is 1-3 μm and the purity is 99%;

[0076] Step 2: The mixed slurry obtained in Step 1 is evaporated at 1300 r / min and 210℃, and then ground to obtain a mixed powder with uniform particle size and greater than 100 mesh.

[0077] Step 3: The mixed powder obtained in Step 2 was calcined at 1200℃ in an oxygen atmosphere for 8 hours, and then cooled to room temperature in the furnace to obtain Nb2Hf6Ta2O in powder form. 22 Thermal barrier coating materials;

[0078] Step 4: Add a 1% (w / w) polyvinylpyrrolidone solution to the Nb2Hf6Ta2O powder from Step 3. 22 The thermal barrier coating material is granulated and sieved to obtain agglomerated powder with a sieve mesh size of 100-200 mesh. The mass of the binder incorporated accounts for a certain percentage of the Nb2Hf6Ta2O powder obtained in step 3. 22 0.2% of the mass of the thermal barrier coating material;

[0079] Step 5: The agglomerated powder obtained in Step 4 is pre-pressed at 150 MPa to obtain a green body. Then, the green body is cold isostatically pressed at 180 MPa for 25 min to obtain Nb2Hf6Ta2O. 22 Ceramic blank;

[0080] Step 6: Take the Nb2Hf6Ta2O obtained in Step 5 22 The ceramic body was held at 500℃ for 6 hours in air to remove the binder, then calcined at 1600℃ for 7 hours and cooled to room temperature in the furnace to obtain bulk Nb2Hf6Ta2O. 22 Thermal barrier coating materials.

[0081] The bulk Nb2Hf6Ta2O 22 The fracture toughness of the thermal barrier coating material is 2.41 ± 0.38 MPa·m. 1 / 2 .

[0082] Example 5

[0083] A Ti2Hf6Ta2O 21 A thermal barrier coating material, wherein the raw materials of the thermal barrier coating material include TiO2, HfO2 and Ta2O5, wherein the molar ratio of TiO2, HfO2 and Ta2O5 is 2:6:1.

[0084] A Ti2Hf6Ta2O 21 The preparation method of thermal barrier coating materials includes the following steps:

[0085] Step 1: TiO2, HfO2 and Ta2O5 with a raw material molar ratio of 2:6:1 are wet ball-milled at 320 r / min for 8 h to obtain a mixed slurry; the particle size of TiO2, HfO2 and Ta2O5 is 1-3 μm and the purity is 99%;

[0086] Step 2: The mixed slurry obtained in Step 1 is evaporated at 1500 r / min and 220℃, and then ground to obtain a mixed powder with uniform particle size and greater than 100 mesh.

[0087] Step 3: The mixed powder obtained in Step 2 was calcined at 1200℃ in air for 7 hours, and then cooled to room temperature in the furnace to obtain Ti2Hf6Ta2O powder. 21 Thermal barrier coating materials;

[0088] Step 4: Add a 2% (w / w) polyvinyl alcohol solution to the Ti2Hf6Ta2O powder from Step 3. 21 The thermal barrier coating material is granulated and sieved to obtain agglomerated powder with a sieve mesh size of 100-200 mesh. The mass of the binder incorporated accounts for a certain percentage of the Ti2Hf6Ta2O powder obtained in step 3. 21 0.4% of the mass of the thermal barrier coating material;

[0089] Step 5: The agglomerated powder obtained in Step 4 is pre-pressed at 100 MPa to obtain a green blank, and then the green blank is cold isostatically pressed at 150 MPa for 30 min to obtain Ti2Hf6Ta2O. 21 Ceramic blank;

[0090] Step 6: Take the Ti2Hf6Ta2O obtained in Step 5 21 The ceramic body was placed in air and held at 500℃ for 6 hours to remove the binder, followed by calcination at 1800℃ for 8 hours, and then cooled to room temperature in the furnace to obtain bulk Ti2Hf6Ta2O. 21 Thermal barrier coating materials.

[0091] The bulk Ti2Hf6Ta2O 21 The fracture toughness of the thermal barrier coating material is 2.44 ± 0.33 MPa·m. 1 / 2 .

[0092] Comparative Example 1

[0093] A type of Hf6Ta2O 17 The preparation method of thermal barrier coating materials includes the following steps:

[0094] Step 1: The raw materials HfO2 and Ta2O5 in a molar ratio of 6:1 are wet ball-milled at 320 r / min for 7 h to obtain a mixed slurry; the particle size of HfO2 and Ta2O5 is 1-3 μm and the purity is 99%;

[0095] Step 2: The mixed slurry obtained in Step 1 is evaporated at 1200 r / min and 200℃, and then ground to obtain a mixed powder with uniform particle size and greater than 100 mesh.

[0096] Step 3: The mixed powder obtained in Step 2 was calcined at 1200℃ in air atmosphere for 6 hours, and then cooled to room temperature in the furnace to obtain Hf6Ta2O in powder form. 17 Thermal barrier coating materials;

[0097] Step 4: Add a 1% (w / w) polyvinyl alcohol solution to the Hf6Ta2O powder from Step 3. 17 The thermal barrier coating material is granulated and sieved to obtain agglomerated powder with a sieve mesh size of 100-200 mesh. The mass of the binder incorporated accounts for a certain percentage of the Hf6Ta2O in the powder obtained in step 3. 17 0.2% of the mass of the thermal barrier coating material;

[0098] Step 5: The agglomerated powder obtained in Step 4 is pre-pressed at 120 MPa to obtain a green body, and then the green body is cold isostatically pressed at 200 MPa for 15 min to obtain Hf6Ta2O. 17 Ceramic blank;

[0099] Step 6: Take the Hf6Ta2O obtained in Step 5 17 The ceramic body was placed in air and held at 600℃ for 4 hours to remove the binder, followed by calcination at 1700℃ for 6 hours. It was then cooled to room temperature in the furnace to obtain bulk Hf6Ta2O. 17 Thermal barrier coating materials.

[0100] The bulk Hf6Ta2O 17 The fracture toughness of the thermal barrier coating material is 1.78 ± 0.05 MPa·m. 1 / 2 .

[0101] See Figure 1 As can be seen from the XRD pattern, the bulk Me prepared in this invention... x Hf6Ta2O 17+y Thermal barrier coating materials are limited to quaternary oxides Me x Hf6Ta2O 17+y The pure phase, with no impurity peaks representing Me oxides observed, indicates that all thermal barrier coating material powders formed a solid solution, and that all Me ions had been converted to Me through solid-phase reactions.x Hf6Ta2O 17+y Me x Hf6Ta2O 17+y The characteristic peaks of thermal barrier coating materials are significantly different from those of pure phase Hf6Ta2O. 17 There was a slight shift, which is due to Me atoms doping into Hf6Ta2O. 17 This leads to lattice distortion and changes in unit cell parameters, causing Me x Hf6Ta2O 17+y Thermal barrier coating materials have superior fracture toughness.

[0102] See Figure 2 As can be seen from the SEM image, the Zr3Hf6Ta2O in Embodiment 1 of the present invention is a block. 23 The thermal barrier coating material has a dense, non-porous surface and a large number of elongated grain structures. These structures can be pulled out during crack propagation, consuming the strain energy during crack propagation and thus hindering further crack propagation, resulting in a bulk Zr3Hf6Ta2O structure. 23 The fracture toughness of the thermal barrier coating material is improved; the bulk Me prepared in Examples 2-5 x Hf6Ta2O 17+y The morphology and structure of the thermal barrier coating material are similar to those in Example 1.

[0103] See Figure 3 As can be seen from the TEM image, the bulk Zr3Hf6Ta2O prepared in Example 1 of this invention... 23 The thermal barrier coating material contains elements Hf, Zr, Ta and O, and each element is evenly distributed without element segregation or agglomeration, which reduces local defects and stress concentration, and the fracture toughness of the material surface is consistent.

Claims

1. A method for preparing a high fracture toughness, long-period quaternary oxide thermal barrier coating material, characterized in that, Includes the following steps: Step 1: Me x O y HfO2 and Ta2O5 were wet-milled to obtain a mixed slurry; the Me x O y It is one of ZrO2, Gd2O3, Y2O3, Nb2O5, and TiO2; measured in molar ratios, Me x O y HfO2:Ta2O5 = (1-3):6:1; the Me x O y The particle size of HfO2 and Ta2O5 is 1-3 μm; Step 2: Heat and dry the mixed slurry obtained in Step 1, then grind it to obtain a mixed powder with a particle size greater than 100 mesh; Step 3: Calcine the mixed powder obtained in Step 2 in an air or oxygen atmosphere at 1100-1300℃ for 6-9 hours to obtain a powder material with high fracture toughness and long period quaternary oxide thermal barrier coating. The thermal barrier coating material is a long-period quaternary single-phase solid solution oxide with the chemical formula Zr3Hf6Ta2O. 23 Gd2Hf6Ta2O 20 Y4Hf6Ta2O 23 Nb2Hf6Ta2O 22 Ti2Hf6Ta2O 21 One of them.

2. The method for preparing a high fracture toughness long-period quaternary oxide thermal barrier coating material according to claim 1, characterized in that: In step 1, Me x O y The purity of the powders of HfO2 and Ta2O5 is ≥99%.

3. The method for preparing a high fracture toughness long-period quaternary oxide thermal barrier coating material according to claim 1, characterized in that: In step 1, the ball milling time is 4-8 hours, zirconium oxide balls are used as the ball milling medium, anhydrous ethanol is used as the liquid medium, the ball-to-material ratio is 3:1, and the rotation speed is 300-350 r / min.

4. The method for preparing a high fracture toughness long-period quaternary oxide thermal barrier coating material according to claim 1, characterized in that: In step 2, a magnetic stirrer is used for heating and drying, with a stirring speed of 1000-1500 r / min and a heating temperature of 180-220℃.

5. The method for preparing a high fracture toughness long-period quaternary oxide thermal barrier coating material according to claim 1, characterized in that, Also includes: Step 4: The adhesive is incorporated into the thermal barrier coating material in step 3 to form granules, and then sieved to obtain agglomerated powder with a sieve mesh size of 100-200 mesh. Step 5: Pre-press the agglomerated powder obtained in Step 4 to obtain a green body; then perform cold isostatic pressing on the green body to obtain a ceramic body. Step 6: Remove the binder from the ceramic preform obtained in Step 5, then calcine it at 1500-1800℃ for 6-9 hours, and cool it to room temperature in the furnace to obtain a blocky high fracture toughness long-period quaternary oxide thermal barrier coating material.

6. The method for preparing a high fracture toughness long-period quaternary oxide thermal barrier coating material according to claim 5, characterized in that: In step 4, the adhesive is a polyvinyl alcohol solution or a polyvinylpyrrolidone solution, with a mass fraction of 1-3%, and the mass of the adhesive incorporated accounts for 0.2-0.6% of the mass of the thermal barrier coating material in powder form in step 3.

7. The method for preparing a high fracture toughness long-period quaternary oxide thermal barrier coating material according to claim 5, characterized in that: The pressure for pre-pressing in step 5 is 100-150 MPa; the pressure for cold isostatic pressing is 150-280 MPa, and the holding time is 10-30 min.

8. The method for preparing a high fracture toughness long-period quaternary oxide thermal barrier coating material according to claim 5, characterized in that, The glue removal operation in step 6 specifically involves placing the ceramic body in an air or oxygen atmosphere and keeping it at 400-600℃ for 4-6 hours.

Citation Information

Patent Citations

  • A type A2B2O7 rare earth tantalate ceramic and its preparation method

    CN111925211B

  • TiSi2 doped Gd2Zr2O7 ceramic material, preparation method and thermal barrier coating

    CN114368969A

  • Thermal barrier coating

    US20210047968A1